PENINGKATAN KESEJAHTERAAN RUMAH TANGGA NELAYAN MELALUI PENGELOLAAN DAN PENGEMBANGAN HASIL PERIKANAN DI MEULABOH PROVINSI ACEH - Yasrizal Yasrizal (Universitas Teuku Umar, 2018)
The main problem is the high level of poverty in coastal communities due to captured fishery products being sold directly to retailers and traders so that the value obtained is relatively low. Production of capture fisheries products can increase fishermen's household income for that it is necessary to increase additional skills for fishermen households in processing fisheries. The purpose of this activity is to improve the purpose of this activity is to transfer the knowledge of processing fishery products to fishermen households in an effort to increase household income of fishermen and coastal communities. The method of activities carried out is training in the form of explanation of fisheries processing materials, fisheries product processing assistance, fishery product packaging and fishery products production. Products that are processed are meatballs and nagets made from fish. Meulaboh community looks enthusiastic in processing fishery products, there are community efforts to produce processed fishery products.